Social connectedness and well-being of elderly customers: Do employee-to-customer interactions matter?. Issue 2 (17th February 2023) - Feng, Kuo; Altinay, Levent; Alrawadieh, Zaid
ABSTRACT: While a plethora of research examines the antecedents and outcomes of favorable employee-to-customer interaction in the hospitality industry, little empirical investigation has been conducted so far to understand the effect of employee-to-customer interaction on customers' social well-being. This omission is particularly intriguing in the context of elderly care homes whereby employee-to-customer interaction is both intense and crucial. Building on a transformative service research perspective, the present study draws on a mixed-methods approach using a sequential quantitative-qualitative design to understand the interface between favorable employee-to-customer interaction, social connectedness, and social well-being. Using data from 267 elderly individuals in care homes combined with data from three focus groups in China, the study confirms the role of favorable employee-to-customer interaction in enhancing the social connectedness of elderly customers. Both employee-to-customer interaction and social connectedness are also found to positively influence elderly customers' social well-being. Findings from the qualitative study lend support to the proposed theoretical model and further demonstrate how elderly consumers' social well-being is impacted in a transformative way by favorable interactions with employees. Qualitative findings show how both employees and elderly customers deploy different resources to pursue transformative outcomes of value exchange and value co-creation. The study advances transformative service research and suggests implications for policy and managers in elderly care homes and the wider hospitality industry.